Compilers : principles, techniques, and tools - Aho, Alfred V.; Sethi, Ravi;Ullman, Jeffrey D. (Massachusetts : Addision-Wesley Publishing Company, 1985)
This book is a descendant of Principles of compiler design. The emphasis sis on solving problems universally encountered in designing a language translator, regardless of the source or target machine.
Chapter 1. Introduction to compiling -- Chapter 2. A simple one-pass compiler -- Chapter 3. Lexical analysis -- Chapter 4. Syntax analysis -- Chapter 5. Syntax-directed translation -- Chapter 6. Type checking -- Chapter 7. Run-time environments -- Chapter 8. Intermediate code generation -- Chapter 9. Code generation -- Chapter 10. Code Optimization -- Chapter 11. Want to write a compiler? -- Chapter 12. A look at some compiler.
Includes bibliographical references and index.
Keywords: COMPILING (ELECTRONIC COMPUTERS)